Indicadores preliminares para a constituição do sujeito leitor/escritor - Reis, Beatriz Pires (2011)
Introduction: Speech therapists have recently extended their performance beyond private clinics. Being part of the Family Health Teams, these professionals are summoned to develop actions promoting health, quality of life and disease prevention. Working at the Basic Health Units, speech therapists have identified an increase in demand for assistance addressing deficit areas in reading and writing, these increased demand motivated them to investigate the origin of these problems and propose solutions for them. Aim: to construct clinical risk indicators for the constitution of the subject writer, based on the Language Symptoms Organization Model and the Four Pillars of the Constitution of the Subject Writer. Methods: Survey of 102 speech-language academic reports of subjects assisted at three Basic Health Units located in the Eastern Zone of São Paulo, with recognized concerns in reading and writing. The subjective data regarding the children s writing were extracted from interviews between parents and speech therapists, and speech therapist s evaluation, and analyzed with the proposed theoretical approach adopted. Results and conclusion: From the analysis, 15 Preliminary Indicators for the Constitution of the Subject Reader/Writer were deployed, not establishing a direct relationship between absence and symptom, therefore, should be used to promote health. It is intended that such indicators, once tested and validated, serve to modify the threat that accompanies the school age children and worries parents and speech therapists, teachers and professionals who are part of the Family Health Teams